Expression of Serum Exosomal MicroRNA-21 in Human Hepatocellular Carcinoma - Wang, Hongwei (Hindawi Publishing Corporation, 2014)
New strategies for the diagnosis of hepatocellular carcinoma (HCC) are urgently needed. There is an increasing interest in using microRNAs (miRNAs) as biomarkers in diseases. In this study, we examined the expression of miR-21 in serum exosomes from patients with HCC or chronic hepatitis B (CHB) and investigated the potential clinical significance of miR-21. Quantitative RT-PCR indicated that the concentration of miR-21 was significantly higher in exosomes than in exosome-depleted supernatants or the whole serum. Further, the expression level of serum exosomal miR-21 was significantly higher in patients with HCC than those with CHB or healthy volunteers (P < 0.0001, P < 0.0001, resp.). High level of miR-21 expression correlated with cirrhosis (P = 0.024) and advanced tumor stage (P = 0.001). Although serum level of miR-21 was higher in patients with HCC than in patients with CHB and healthy volunteers, the sensitivity of detection is much lower than using exosomal miR-21. These findings indicate that miR-21 is enriched in serum exosomes which provides increased sensitivity of detection than whole serum. Exosomal miR-21 may serve as a potential biomarker for HCC diagnosis.